The Effect of the Implementation of “Veronika” Virtual Assistant Chatbot on Customer Experience and Satisfaction in Using Telkomsel Service - Zakaria, Muchammad Hatta; Boer, Rino Febrianno (Budapest International Research and Critics University, 2022)
Technology development creates new media so humans can communicate with chatbots to meet the need for information. All customer needs, from submitting customer complaints to service access, can be done quickly using a chatbot. Currently, in Indonesia, several large companies have adopted chatbots to make it easier for customers to get customer service on a self-service basis or without human assistance. This study aims to analyze the effect of Veronika's chatbot implementation on self-service technology experience and the effect of self-service technology experience on self-service technology satisfaction in Telkomsel. This study uses a quantitative approach with a survey method. The results show that customer experience using chatbots is significantly influenced by perceived usefulness when interacting with Veronika's chatbot. This experience significantly influences customer satisfaction in using Telkomsel services.